Strengthening Paralegal Capacity Among The Cadres of 'Aisyiyah Branch Leadership (PCA) Rungkut Surabaya to Promote Legal Awareness - Yustitianingtyas, Levina; Pratiwi, L.Ya Esty (Universitas Muhammadiyah Magelang, 2025)
This community service program aimed to strengthen grassroots legal awareness by enhancing the capacity of women leaders in the 'Aisyiyah Branch Leadership (PCA) Rungkut, Surabaya, through structured paralegal training. The program utilized the Asset-Based Community Development (ABCD) approach and consisted of participatory sessions on basic legal knowledge, human rights, and advocacy skills. A total of 30 participants engaged in a three-session training, with evaluation conducted through post-tests and qualitative reflection. The results showed a substantial improvement in legal understanding. Participants also demonstrated growing confidence and critical awareness of legal rights and responsibilities. Qualitative findings revealed a shift in perception, as participants began to see themselves as legal actors capable of community advocacy. Post-training will initiatives included the formation of a cross-sector paralegal network and the establishment of a community legal aid post (Posbakum) in the PCA Rungkut area. This initiative contributed to the realization of the Qoryah Thayyibah Village model as a justice-oriented, legally aware community. The program illustrates how faith-based women’s organizations can serve as effective drivers of grassroots legal empowerment and access to justice.